Risks of oesophageal cancer in Zimbabwe: Eating habits and indoor air pollution from firewood smoke - Kadzatsa, Webster; Mazhindu, Tinashe; Chadyiwa, Martha (Archives of Community Medicine and Public Health, 2023)
Background: Oesophageal cancer is among the top five (5) cancers in Zimbabwe, and it has a high mortality rate. Several studies have alluded to the association between exposure to firewood smoke and this cancer. This study assessed the association between firewood smoke exposure, consumption of hot beverages, and food with oesophageal cancer among cancer patients in Zimbabwe. Methods: This study was quantitative in nature and adopted a cross-sectional design. A matched case-control approach with 95 pairs of cases and controls from Parirenyatwa Group of Hospitals’ Radiotherapy Centre, a major referral hospital in Zimbabwe was used. A total of 190 participants were interviewed using a questionnaire administered via telephone by trained interviewers. Secondary data using histology results and radiology reports were obtained from the patient’s medical records. SPSS version 27 was used to perform the descriptive analysis for variables such as age, marital status, exposure to firewood smoke, and thermal burns. Bivariate and multivariate analyses were used to examine the relationship between oesophageal cancer and dependent variables. Results: The ratio of male to female OC cases was 1.4 to 1, with a mean age of 63 for males and 60 years for females. The OC was significantly associated with the usage of firewood smoke as a major source of cooking energy (OR: 2.961; 95 % CI 1.46 - 6.03) (AOR: 4.22; 95% CI 1.22 - 14.59) with a p - value of 0.043. Also, the OC was significantly associated with high consumption of sweet potatoes (OR: 3.26; 95 % CI:1.67 - 6.55) (AOR: 3.47; 95% CI: 1.07 - 11.23) with a p. - value of 0.001. The co-usage of the kitchen as a dining room was associated with OC (OR: 2.65; 95% CI: 1.44 - 4.88), no association was found (AOR: 0.98; 95% CI: 0.34 - 2.72) after adjusting for confounders. Risk factors such as age, alcohol intake, smoking, HIV status, and marital status were not associated with OC. Conclusion: The use of firewood for cooking and the consumption of sweet potatoes are the major contributors to OC among Zimbabweans. Awareness of the eating habits of sweet potatoes and using the kitchen as a dining area could significantly reduce cases of OC among Zimbabweans.